2018
DOI: 10.1007/s00264-018-3927-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for medical complications after long-level internal fixation in the treatment of adult degenerative scoliosis

Abstract: Heart disease comorbidity is an independent risk factor for both medical and major medical complications. Smoking, fusion level, and LOS are independent risk factors for medical complication. Diabetes is the independent risk factors for major medical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Owing to the fact that most of our patients were relatively young, there was relatively little data on history of lumbar operation, previous medication use, or whether there were any ageassociated comorbidities such as diabetes and osteoporosis, some of which could be potential risk factors for ADS. Several studies have reported a direct correlation between parameters such as the ASA grade, Cobb angle, total operation time, PT, level of fusion, LOS, staging, multiple surgeries and the incidence of perioperative complications in ADS [9,[19][20][21][22]. However, further research is needed to identify the risk factors for perioperative complications in adult non-degenerative scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the fact that most of our patients were relatively young, there was relatively little data on history of lumbar operation, previous medication use, or whether there were any ageassociated comorbidities such as diabetes and osteoporosis, some of which could be potential risk factors for ADS. Several studies have reported a direct correlation between parameters such as the ASA grade, Cobb angle, total operation time, PT, level of fusion, LOS, staging, multiple surgeries and the incidence of perioperative complications in ADS [9,[19][20][21][22]. However, further research is needed to identify the risk factors for perioperative complications in adult non-degenerative scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…This had been well reported in lumbar spinal fusion surgery with an increased rate of pseudoarthrosis, occurring up to four times in smokers compared with nonsmokers after lumbar spinal fusion. [3][4][5][6] Hilibrand and colleagues demonstrated poorer clinical outcomes among smokers when compared with nonsmokers in anterior cervical decompression and fusion. They postulated that the poorer outcomes were because of fusion-related complications as they found a strong association between the development of pseudoarthrosis and poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The operation of DS is often accompanied by a high risk of complications due to older age, osteoporosis, and other organ diseases [ 28 ]. The prevalence of revision is an important index to test the complications.…”
Section: Discussionmentioning
confidence: 99%